Biology and Population Dynamics of the American Vine Moth and the Potential Biocontrol with Trichogramma pretiosum - Costa-Lima, Tiago Cardoso da; Araujo, Ana Taires Pereira de; Torris, Aline Finotti [UNESP] (Entomological Soc Brasil, 2021)
The American grapevine moth (AGVM), Lasiothyris luminosa (Razowski & Becker) (Lepidoptera: Tortricidae), was recently registered as a new pest for table grapes in the Northeast region of Brazil. In the present study, two approaches were made aiming to aid information to support management strategies for the new pest control: (i) study AGVM biology in the laboratory and its population dynamics in the field and (ii) evaluate Trichogramma pretiosum Riley as a potential biological control method against L. luminosa. The AGVM population dynamics showed a similar trend in the three grapevine monitored vineyards. The larvae started occurring at 30 days after pruning (DAP), pre-bloom stage, with a peak population between 54 and 78 DAP, following a decrease until harvest. The AGVM females larva, pupa, and egg-adult period were longer than males. The egg-adult period was 42.1 and 45.2 days for male and females, respectively. Trichogramma pretiosum was able to parasitize L. luminosa eggs. The T. pretiosum egg-adult period was 10.2 days with a 98.5% pupa survivorship at 25 degrees C. The release of T. pretiosum in the vineyards resulted in 65.5 to 73.2% AGVM egg parasitism. Our findings bring the first biological and population dynamics information for L. luminosa, which can help developing efficient approaches to monitor and control the pest in grapevines. The release of T. pretiosum in the vineyard is a potential biological control option to AGVM.
Keywords: Lasiothyris luminosa; Tortricidae; egg parasitoid; table grapes; Brazil